An acoustic education : evaluating soundwalks and listening exercises in promoting aural awareness and sensitivity in landscape architecture education - Jarquio, Samantha M. (Kansas State University, 2013)
Sound has always been an integral part of the outdoor environment. However, since the onset of the Industrial Revolution, and given the continual emergence of new technological sounds, society’s aural awareness and sensitivity has continued to decrease (Schafer, 1977). While the visual often dominates the perception of the outdoor environment – especially within the design field – all five senses are vital to a holistic experience. A greater emphasis on sound in landscape architecture is critical as landscape architects move toward a more holistic approach to designing the outdoor environment. The primary learning objective of this thesis was to evaluate the effectiveness of soundwalks and listening exercises for landscape architecture students, as a way to increase their aural awareness and sensitivity. The first part of this study established the current status and need for an acoustic education in landscape architecture by examining university course offerings and surveying professionals and faculty members in the field. The remainder of the study involved a listening experiment conducted with landscape architecture students from Kansas State University. Participants were assessed on their ability to listen to and analyze sounds before and after participating in soundwalks, listening exercises, and lessons in interdisciplinary sound terminology. This study provides a clearer understanding of the role of sound in landscape architecture and, more broadly, the environment. The surveys revealed that respondents more often consider sound as noise to be mitigated rather than as inspiration for design. Respondents also indicated that sound is an important consideration in design and that an acoustic component can be valuable in landscape architecture education. Those who participated in the listening experiment also indicated that an acoustic education, including soundwalks and listening exercises, can be effective in increasing aural awareness and sensitivity. While this study did not explore all approaches to an acoustic education, it provides a suitable point of departure for future related research.
Keywords: Acoustic education; Landscape architecture education; Soundscape; soundwalk; Listening exercise; Landscape Architecture (0390)